Implementation of Local Content Learning Media in Elementary Schools: A Study Illustration Book - Al-Pajri, Muhammad Rezki Ramdhani; Jayadi, Karta; Syahrir, Nurlina (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study intends to implement the illustrated book "The Story of the Origin of the Name Jeneponto" as a local content learning media in class VI public elementary school 4 Bangkala. This book has been designed using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. However, in the design process, it was only carried out up to the analysis, design, and development stages. The research method used is research and development with a quantitative-descriptive approach, involving questionnaires, interviews, and observation techniques. The results of the study show that this illustrated book is effective in increasing students' interest in learning about the local history of Jeneponto. The attractive visual appearance and stories that are relevant to local culture make this book easier to understand. As many as 75% of students feel more interested in learning history after using this book. In addition, teachers stated that this book creates a pleasant learning atmosphere and supports the preservation of local culture. This study provides an important contribution to the development of visual-based learning media, which is relevant to preserving local wisdom and strengthening cultural identity among the younger generation.